Cultural Competency and Surgical Decision Making in Otolaryngology. (May 2022) - Ovrom, Erik; Zemene, Yilkal; Gerndt, Sophie; Andrade, Victor; Wiedermann, Joshua
Given the high prevalence of otolaryngology infections such as tonsillitis, otitis, and pharyngitis in low and middle income countries, the field of global otolaryngology continues to grow to accommodate patients around the world. This commentary focuses on best practices in transcultural communications between US doctors and foreign patients with an emphasis on cultural competency. We use alternative medicine as an exemplar for how to collaborate with patients to develop treatment plans that respect their cultural beliefs and lifestyles. Rather than assigning value to the patient's alternative medicine practices, we believe that instructing and counseling a patient on how to incorporate follow-up visits and rehabilitation after allopathic medical procedures such as surgical tonsillectomy should be done in a way that respects the patient's preexisting health regimen. By doing so, these new aspects of their health care will take a discrete place in their wellness practices and engender more trust and better health outcomes.